Fallout of Lead Over Paris From the 2019 Notre‐Dame Cathedral Fire. (21st August 2020) - van Geen, Alexander; Yao, Yuling; Ellis, Tyler; Gelman, Andrew
Abstract: The roof and spire of Notre‐Dame cathedral in Paris that caught fire and collapsed on 15 April 2019 were covered with 460 t of lead (Pb). Government reports documented Pb deposition immediately downwind of the cathedral and a twentyfold increase in airborne Pb concentrations at a distance of 50 km in the aftermath. For this study, we collected 100 samples of surface soil from tree pits, parks, and other sites in all directions within 1 km of the cathedral. Concentrations of Pb measured by X‐ray fluorescence range from 30 to 9, 000 mg/kg across the area, with a higher proportion of elevated concentrations to the northwest of the cathedral, in the direction of the wind prevailing during the fire. By integrating these observations with a Gaussian process regression model, we estimate that the average concentration of Pb in surface soil downwind of the cathedral is 430 (95% interval, 300–590) mg/kg, nearly double the average Pb concentration in the other directions of 240 (95% interval, 170–320) mg/kg. The difference corresponds to an integrated excess Pb inventory within a 1 km radius of 1.0 (95% interval, 0.5–1.5) t, about 0.2% of all the Pb covering the roof and spire. This is over 6 times the estimated amount of Pb deposited downwind 1–50 km from the cathedral. To what extent the concentrated fallout within 1 km documented here temporarily exposed the downwind population to Pb is difficult to confirm independently because too few soil, dust, and blood samples were collected immediately after the fire. Plain Language Summary: This study attempts to estimate the extent to which the population of Paris was exposed to lead as a result of the Notre‐Dame cathedral fire of 15 April 2019. The concern stems from the large quantity of lead that covered the cathedral, some of which was injected into the air by the fire for several hours. In order to evaluate how much lead rising from the fire was redeposited nearby, surface soil samples were collected in all directions within a 1 km radius of the cathedral. Elevated levels of lead observed downwind of the cathedral indicate that surface soil preserved the mark of lead fallout from the fire. Although the estimated amount of lead redeposited within 1 km corresponds to only a small fraction of the total covering the cathedral, it could have posed a health hazard to children located downwind for a limited amount of time. Environmental testing on a larger scale immediately after the fire could have provided a more timely assessment of the scale of the problem and resulted in more pointed advice to the surrounding population on how to limit exposure to the fallout of lead. Key Points: Surface soil Pb concentrations within 1 km of Notre‐Dame cathedral are about 200 mg/kg higher downwind of the fire relative to background The corresponding fallout of 1, 000 kg Pb is 6 times higher than the estimated mass of Pb from the fire transported by the wind beyond 1 km The resulting human exposure was probably dwarfed by the impact of leaded gasoline in previous decades but warranted more testing sooner